MODERN CONCEPTS OF THE RESTAURANT INDUSTRY AND THE IMPLEMENTATION OF PET-FRIENDLY POLICIES - STUKALSKA, NATALIIA; MAMCHENKO, LIUDMYLA; NIEMIRICH, OLEKSANDRA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article analyzes foreign and domestic experience in the implementation of pet-friendly policies by restaurant establishments as a reflection of their conceptual essence and a way to ensure customer loyalty. In many countries, including Ukraine, an increase in the number of people who keep pets reflects a general trend toward the humanization of society and rising standards of living. This category of people often treats their pets as full-fledged family members, devoting considerable time and attention to them, including spending leisure time at restaurant establishments. It is shown that a loyal attitude from restaurant businesses toward customers with pets is an important element in ensuring the competitiveness of the hotel and restaurant industry as a whole. Based on the analysis of factual material (empirical data) , it is argued that in the United States and European Union countries, a certain share of restaurant establishments incorporate pet-friendly policies as a key element of their overall concept, which has led to the emergence of cafés specifically oriented toward customers with pets. The authors also analyze the experience of Ukrainian restaurant establishments implementing pet-friendly policies. It was found that the largest share of such businesses is understandably concentrated in large cities such as Lviv, Kyiv, and Odesa. This issue is also relevant for Ukraine, and its timely resolution would help effectively manage existing and potential conflicts of interest between pet owners and other patrons, as well as ensure compliance with all HACCP requirements and standards. Awareness among restaurant owners and managers of the value of the pet-friendly customer segment enables the strategic use of these policies as a competitive advantage in the restaurant services market. Key challenges in this context include adherence to necessary guidelines for ensuring comfort for all guests, the proper organization of space, and additional staff training to manage customer service and resolve potential conflicts.